A New Modular, Autonomously Reconfigurable Manipulator Platform. (16th June 2015) - Kereluk, Jason A.; Emami, M. Reza
This paper discusses the design and development of a new Modular, Autonomously Reconfigurable Serial manipulator platform for advanced manufacturing, termed as the MARS manipulator. The platform consists of i) an 18-Degree-of-Freedom (DOF) serial-link manipulator capable of locking any of its joints at any position in their continuous range, such that it can emulate fewer-DOF serial manipulators with different kinematic and dynamic parameters, and ii) an integrated simulation and design environment that provides control over the manipulator hardware as well as a toolset for the design, implementation and optimization of a desired manipulator configuration for a given task. The effectiveness of the MARS manipulator to adapt its configuration to various tasks is examined by assuming two well-known configurations, SCARA and articulated, and by performing a specific task with each of them. The variation in effectiveness of the two configurations in terms of the end-effector trajectory, end-effector accuracy and power consumption is discussed. Further, these configurations are optimized with respect to their performance accuracy, and compared to their pre-optimized versions. Finally, the accuracy model of the simulation is compared against the physical hardware system, running the same task.